Ogilvie syndrome presenting with septic shock - Özsoylu, Serkan; Akyıldız, Başak Nur; Dursun, Adem (The Turkish Journal of Pediatrics, 2018)
Acute colonic pseudo-obstruction (ACPO) is also known as Ogilvie`s. We report a 10-year-old child with an unremarkable past history who presented with septic shock including hypotension, prolonged capillary refill time, decreased urine output ( < 0.5 ml/kg/h), metabolic acidosis, liver failure, respiratory failure. The symptoms resolved with supportive therapy. In our patient septic shock contributed to Ogilvie syndrome. Although it is a rare condition in pediatric population, pediatricians should be aware of children with abdominal distention; supportive management is successful and morbidity/mortality is minimal.
Keywords: Ogilvie syndrome; dialysis; septic shock